(untitled) (Journal of the Bangladesh Agricultural University, 2018)
The main purposes of the study were to assess the extent of participation of rural women in homestead vegetable cultivation at Monirampur upazila under Jessore district and to explore the relationship between each of the selected characteristics of the rural women and their extent of participation in homestead vegetable cultivation. The study was limited within three selected villages namely, Nehalpur and Panchakori of Nehalpur union and Jhanpa of Jhanpa union. Data were collected from randomly selected 60 respondents during the period of 04 September to 17 October, 2016. Appropriate scales were used to measure the variables of the study. Correlation(s) test was used to ascertain the relationships between the concerned independent variables and dependent variable. About half (48.3 percent) of the rural women had low to medium participation in vegetable cultivation compared to 3.34 percent having high participation. Considering broadly selected 6-aspects of homestead vegetable cultivation, the rural women’s participation was highest in seedbed preparation and raising of seedlings, while it was lowest in case of intercultural operation. In case of 26-issues, the most dominant area of rural women’s participation was seed collection while it was least in case of training. Only age out of eleven selected characteristics had the significant positive relationship with their participation in homestead vegetable cultivation. It might be concluded from the gist findings that, the participation of women in homestead vegetable production is still not satisfactory and necessary steps concerning extension approach should be taken to increase the vegetable production by ensuring barrier-free participation J. Bangladesh Agril. Univ. 16(1): 17-22, April 2018